2014
DOI: 10.1002/elps.201300544
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic mobilities of neutral analytes and electroosmotic flow markers in aqueous solutions of Hofmeister salts

Abstract: Small neutral organic compounds have traditionally the role of EOF markers in electrophoresis, as they are expected to have zero electrophoretic mobility in external electric fields. The BGE contains, however, ions that have unequal affinities to the neutral molecules, which in turn results in their mobilization. In this study we focused on two EOF markers-thiourea and DMSO, as well as on N-methyl acetamide (NMA) as a model of the peptide bond. By means of CE and all atom molecular dynamics simulations we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The Raman-MCR experiments and q computations are described in Supplementary Section 3 (Supplementary Figs. [41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The Raman-MCR experiments and q computations are described in Supplementary Section 3 (Supplementary Figs. [41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The electrophoresis procedure was identical to that described in our previous study [26], based on the mobility measurement method introduced by Williams and Vigh [27]. Every new capillary was conditioned with 1.0 M sodium hydroxide for 20 min, with deionized water for 10 min, and with BGE for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research, we have found that small neutral marker molecules can be mobilized, even by small inorganic ions [26]. This mobilization has not been accounted for in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Third, in contrast to other electrophoretic detection methods, it requires no background electrolyte and/or pH buffer that may lend charge to small neutral entities. 27 29 Finally, the technique works well at low salt (and polymer) concentrations where direct ion–solute interactions dominate and screening effects are less significant. Ion binding at PNIPAM-covered model surfaces has often been studied, 30 33 but there is a lack of observations in dilute (here, at 10 mM monomer equivalent, therefore with no interactions between the extended chains) bulk solutions.…”
Section: Introductionmentioning
confidence: 99%